**Question:**I keep ending up with (-4) as the answer, but the real answer is (0).

Can you show me step by step how to work it out? I don't usually have any trouble with these types of problems...

Thank you!

**Answers:**

2(5-x)-(-2)(x-3)=-(3x-4)

10-2x+2x-6=-3x+4

10-6=-3x+4

4=-3x+4

4-4=3x

0=3x

0/3=x

0=x

i hope that helps. you just need to make sure you keep track of the negatives and positives. good luck

First, let's distribute to clear parentheses:

10-2x +2x - 6 = -3x +4 , really pay attention to the signs!

4 = -3x +4

-3x = 0, divide by 3 and yes, the answer is 0.

You probably made an error with the signs.

Hope this helps!

10 - 2x - (-2x + 6) = -3x + 4

10 - 2x +2x -6 = -3x + 4

10 - 6 = -3x + 4

4 - 4 = -3x

0 = -3x

0 = x

10-2x-(-2x+6)=-3x+4

10-2x+2x-6=4-3x

4=4-3x

0=3x

x=0

1. 2(5-x) = (10-2x) and (-2)(x-3) = (-2x+6)

Your new equation is (10-2x) - (-2x+6) = -(3x-4)

2. Rewrite it as (10-2x)+(-1)(-2x+6) = -(1)(3x-4)

Which is also (10-2x)+(2x-6) = -3x+4

3. Now add everything together on the left side of the equation

(10-6) + (-2x+2x) = -3x+4

Which gives you [4 + 0x = -3x + 4]

4. Now subtract 4 from both sides to get 0 = -3x

5. Divide each side by -3 (or multiply by -1/3) to get

[0 = x]

You're probably having problems with subtracting the negatives...

2(5 - x) - (-2)(x - 3) = -(3x - 4)

*multiply out the (2), (-2), and negative sign (-)*

(10 - 2x) - (-2 + 6) = (-3x + 4)

*then the subtraction sign applies to everything inside the parenthesis. the (-2 +6)*

10 - 2x + 2x - 6 = -3x + 4

*the 2x's cancel out and you're left with...*

10 -6 = -3x + 4

4 = -3x + 4

*move the four on the left over to the right by adding it's negative to both sides*

(-4) + 4 = -3x + 4 + (-4)

0 = -3x

*divide each side by (-3)*

x=0

This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.

**More Questions & Answers...**